Sympathetic regulation of vascular function in health and disease - Bruno, Rosa Maria; Ghiadoni, Lorenzo; Seravalle, Gino; Dell'Oro, Raffaella; Taddei, Stefano; Grassi, Guido (Frontiers in Physiology, 2012)
The sympathetic nervous system is known to play a pivotal role in short- and long-term regulation of different functions of the cardiovascular system. In the past decades increasing evidence demonstrated that sympathetic neural control is involved not only in the vasomotor control of small resistance arteries but also in modulation of large artery function. Sympathetic activity and vascular function, both of which are key factors in the development and prognosis of cardiovascular events and disease, are linked at several levels. Evidence from experimental studies indicates that the sympathetic nervous system is critically influenced, at the central and also at the peripheral level, by the most relevant factors regulating vascular function, such as nitric oxide, reactive oxygen species, endothelin, the renin-angiotensin system. Additionally, there is indirect evidence of a reciprocal relationship between endothelial function and activity of the sympathetic nervous system. A number of cardiovascular risk factors and diseases are characterized both by increased sympathetic outflow and decreased endothelial function. In healthy subjects, muscle sympathetic nerve activity appears to be related to surrogate markers of endothelial function, and an acute increase in sympathetic activity has been associated with a decrease in endothelial function in healthy subjects. However, direct evidence of a cause-effect relationship from human studies is scanty. In humans large artery stiffness has been associated with increased sympathetic discharge, both in healthy subjects and in renal transplant recipients. Peripheral sympathetic discharge is also able to modulate wave reflection. On the other hand, large artery stiffness can interfere with autonomic regulation by impairing carotid baroreflex sensitivity.